THE EFFECT OF WORK LIFE BALANCE AND WORK STRESS ON EMPLOYEE SATISFACTION - Nabila, Dinda Maulinda; Pratiwi, Reina Dila; Sofyan, Salsabilla Fauziyah; Tobing, Yohanna; Abdurrahman, Gagan Fauzan; Amalia, Shendy (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze the effect of Work-Life Balance and Work Stress in one of the government agencies; City Public Works Department Bandung. The variables used are Work-Life Balance and Work Stress as independent variables, while work satisfaction is the dependent variable. The sample used in this study was 125 employees with a random sampling technique. Data collection methods are primary and secondary data collection. The analysis method uses instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing, and coefficient of determination test. The results of this study indicate that the higher the work-life balance of the employees of the Public Works Department, the higher the level of job satisfaction. Therefore, companies need to pay attention to conflict, work time and improve communication to minimize stress levels. Work-life balance is the dominant variable on work satisfaction. This means that work-life balance is essential in the work system of the employee of the Public Works Department.